The Elements Of Islam And Science: In Traditional Healing In The Ulu Manuscripts Of The Bengkulu Society - Edi Gunawan B; Bilqis Jihan Nabila; Al Mafaza Umami (UIN Fatmawati Sukarno Bengkulu, 2025)
This study aims to describe the coexistence of Islamic and scientific elements in traditional healing in the Ulu Bengkulu manuscript. The study used a qualitative method with a philological approach and text analysis by utilizing the workings of cultural studies. The results showed that the Islamic elements were reflected through the use of words and phrases derived from Islamic knowledge and post-treatment rituals containing spiritual values such as tawakal, intention, and gratitude for healing. The scientific elements were seen in the use of local herbs, simple diagnostic methods, and empirical-based treatment techniques. This healing reflects the harmonization of Islamic teachings as a spiritual foundation and a scientific approach in medical practice. Besides preserving the cultural heritage, this manuscript has the potential to be further developed in the modern medical world, especially through scientific studies of the herbal concoctions and the ethical values contained therein.